2012
DOI: 10.1177/1477370812447265
|View full text |Cite
|
Sign up to set email alerts
|

What determines the trust of immigrants in criminal justice institutions in Europe?

Abstract: This study examines whether the confidence of immigrants in European countries in criminal justice institutions can be explained by two counteracting processes: expectations formed in the country of origin and discrimination experienced in the residence country. The study draws on the pooled waves of the European Social Survey (2002-8), comparing first-and secondgeneration immigrants from 66 countries of origin with natives in 21 residence countries. Multilevel regressions are employed to examine the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
64
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 37 publications
8
64
0
2
Order By: Relevance
“…Yet, there is evidence, indicating that migrants compare experiences and situations in the new country with the country of origin, affecting evaluations of the present situation. For instance, scholars have noted that immigrants tend to judge moral behaviour and treatment by authorities, as well as the trustworthiness of criminal justice institutions relative to standards of their old country (Reese 2001;Menjívar & Bejarano 2004;Röder & Mühlau 2012b). Such findings, we contend, make the support for the expectations hypothesis as for political institutions even more reasonable.…”
Section: Concluding Discussionmentioning
confidence: 51%
“…Yet, there is evidence, indicating that migrants compare experiences and situations in the new country with the country of origin, affecting evaluations of the present situation. For instance, scholars have noted that immigrants tend to judge moral behaviour and treatment by authorities, as well as the trustworthiness of criminal justice institutions relative to standards of their old country (Reese 2001;Menjívar & Bejarano 2004;Röder & Mühlau 2012b). Such findings, we contend, make the support for the expectations hypothesis as for political institutions even more reasonable.…”
Section: Concluding Discussionmentioning
confidence: 51%
“…Röder and Mühlau (2012) found that having moved from a more to a less corrupt country was associated, on average, with more favourable views of police, while Bradford et al (2016) found that immigrants from Africa and South Asia (many of whom will have come from countries with highly corrupt police and political systems) living in England and Wales trusted the police significantly more than non-immigrants. Nannestad et al (2014) report similar findings, and conclude that better 'quality' institutions in destination countries (in their case, Denmark) is linked to higher levels of trust in those institutions among immigrants from countries with lower quality institutions.…”
Section: Institutional Framesmentioning
confidence: 99%
“…Three measures were used to tap into how change in institutional context might shape immigrants assessments of police legitimacy. The first concerned corruption and the rule of law, and here we draw on, and extend, the measure used by Röder and Mühlau (2012). If, as they argue, "immigrants compare the institutional reality of the host country with their experiences of institutions in the home country as a reference point" (ibid: 376), it seems likely that the 'institutional reality' of law and corruption is a particularly salient factor in relation to the police.…”
Section: Measuring Police Legitimacymentioning
confidence: 99%
See 2 more Smart Citations